Strengthening character education through literacy movement at Muhammadiyah junior high school - Zaenab, Siti; Chamisijatin, Lise; Wahyuni, Sri (Journal of Community Service and Empowerment, 2020)
Muhammadiyah Junior High School 02 of Batu city has implemented the Strengthening of Character Education (SBE) through community service program in 2017. It is analyzed that the proram has obstacles in its implementation of classroom-based (SBE), it is proved by the inability of teachers to integrate character values into subjects to match the curriculum content. Thus, it is projected that to improve classroom-based SBE can be done by integrating literacy activities. The classroom-based SBE approach can be implemented through developing instructional method, classroom management, and integrating literacy activities into lesson plan of 2013 Curriculum. This community service program aims to improve SBE through literacy movement at MJHS 02 of Batu City. The method implemented was participation-based method through training and mentoring of SBE, also mentoring to plan and practice the SBE implementation through literacy movement. This program involves school teachers and principle of SMP Muhammadiyah 02 Batu, as many of 16 personnel. Data collection was gathered through observation and document which then analyzed descriptively. Results show that there is an improvement on teachers’ competence in developing lesson plan using classroom-based SBE concept through literacy movement, and an improvement also shown on teachers’ skill in implementing class instruction which is based on 2013 Curriculum that applies SBE through literacy movement. This improvement simultaneously contributes to students’ achievement expected in the 2013 Curriculum, namely character improvement.